2022
DOI: 10.31234/osf.io/x4h7n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Incorrect Cut-Off Values in Autism Screening Tools: The Consequences for Psychological Science

Abstract: The 10-item Autism-Spectrum Quotient (AQ10) is frequently used to screen for high autistic traits in clinical practice and research. For the past decade, however, the National Institute for Health and Care Excellence (NICE) has recommended the use of an incorrect ≥7 cut-off value, instead of the correct ≥6 value specified in the original research on the AQ10. Our inspection of the literature suggests that this discrepancy has proliferated across research, generating confusion over the past decade. After examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Waldren et al (2021) recently reported that the National Institute for Health and Care Excellence (NICE) had, for almost a decade, recommended the incorrect AQ10 cutoff value to screen for autism (≥7 instead of ≥6, based on Allison et al, 2012). This error has generated confusion among researchers and clinicians who administer the AQ10 in their work, with evidence of several studies (e.g., Payne et al, 2020;Rahman et al, 2021) using the incorrect cutoff value (see Waldren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Waldren et al (2021) recently reported that the National Institute for Health and Care Excellence (NICE) had, for almost a decade, recommended the incorrect AQ10 cutoff value to screen for autism (≥7 instead of ≥6, based on Allison et al, 2012). This error has generated confusion among researchers and clinicians who administer the AQ10 in their work, with evidence of several studies (e.g., Payne et al, 2020;Rahman et al, 2021) using the incorrect cutoff value (see Waldren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%